2022
DOI: 10.1002/jcop.22929
|View full text |Cite
|
Sign up to set email alerts
|

The depth of stories: How Black young adults' disclosure of high arousal negative affect in narratives about the COVID‐19 pandemic and the BLM protests improved adjustment over the year 2020

Abstract: The present study investigates whether the way Black young adults constructed their narratives regarding the stressful events of the COVID‐19 pandemic and the black lives matter (BLM) protests related to adjustment over time. A two‐wave mixed prospective and retrospective longitudinal study was conducted in July and December 2020 and included a total of 90 Black young adults. Narrative reports were collected at baseline to determine the psychological interpretations of the two events and were coded based on af… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 60 publications
0
3
0
Order By: Relevance
“…Additionally, only one-third of a nation in a country has a solid awareness of their health (Mahadevan, 2013). Furthermore, it is identified that people who lacked health information literacy skills were more likely to disclose their poor health (Audet et al, 2023). Due to their inability to accurately understand and comprehend health-related information and guidance, those with low health literacy were Healthmisinformation seeking behavior more seriously and frequently afflicted by the COVID-19-driven variations (Audet et al, 2023).…”
Section: Literature Review and Hypotheses Development 21 Social Cogni...mentioning
confidence: 99%
See 2 more Smart Citations
“…Additionally, only one-third of a nation in a country has a solid awareness of their health (Mahadevan, 2013). Furthermore, it is identified that people who lacked health information literacy skills were more likely to disclose their poor health (Audet et al, 2023). Due to their inability to accurately understand and comprehend health-related information and guidance, those with low health literacy were Healthmisinformation seeking behavior more seriously and frequently afflicted by the COVID-19-driven variations (Audet et al, 2023).…”
Section: Literature Review and Hypotheses Development 21 Social Cogni...mentioning
confidence: 99%
“…Furthermore, it is identified that people who lacked health information literacy skills were more likely to disclose their poor health (Audet et al, 2023). Due to their inability to accurately understand and comprehend health-related information and guidance, those with low health literacy were Healthmisinformation seeking behavior more seriously and frequently afflicted by the COVID-19-driven variations (Audet et al, 2023). They may share their medical and health status online with those individuals with limited health expertise, leading them to become a victim of health-misinformation (Lobato et al, 2020).…”
Section: Literature Review and Hypotheses Development 21 Social Cogni...mentioning
confidence: 99%
See 1 more Smart Citation